Sosialisasi Buku Kas Sebagai Solusi Pembukuan Keuangan Digital UMKM Desa Banjaran Kab. Purbalingga - Aning Fitriana; Karunia Zuraidaning Tyas; Anastasia Anggarkusuma Arofah; Nugroho Budi Wirawan (Universitas Tanjungpura, 2023)
MSMEs have an important role in contributing to a country's revenue. In Indonesia, the number of MSMEs is very large, but the majority of MSMEs still do not have good and correct financial management knowledge. There are still many MSMEs who record business transaction activities manually and have not yet led to digitization in bookkeeping. Thus, digital bookkeeping is needed to make it easier for MSME actors to record business transaction activities. This method consists of the preparation, planning, implementation and evaluation stages. In general, the implementation of cash book socialization activities for MSME business actors in Banjaran Village, Purbalingga Regency has been running smoothly and in accordance with the planned program of activities. With this activity, MSMEs business gain new knowledge about managing financial management with a cash book as a digital financial accounting solution. And MSMEs consider the cash book application to be very easy to use and very helpful for MSMEs business in recording transactions when running a business.